Explaining asset pricing puzzles associated with the 1987 market crash - Luca Benzoni; Pierre Collin-Dufresne; Robert S. Goldstein (Federal Reserve Bank of Chicago, 2010)
The 1987 market crash was associated with a dramatic and permanent steepening of the implied volatility curve for equity index options, despite minimal changes in aggregate consumption. We explain these events within a general equilibrium framework in which expected endowment growth and economic uncertainty are subject to rare jumps. The arrival of a jump triggers the updating of agents' beliefs about the likelihood of future jumps, which produces a market crash and a permanent shift in option prices. Consumption and dividends remain smooth, and the model is consistent with salient features of individual stock options, equity returns, and interest rates.
Keywords: G12; G13; 330; Volatility Smile; Volatility Smirk; Implied Volatility; Option Pricing; Portfolio Insurance; Market Risk; Börsenkrise; Capital Asset Pricing Model; Optionspreistheorie; Volatilität; Portfolio-Insurance; Theorie; USA